KONSEPTUALISASI UTILITAS BERDASARKAN TRILOGI VITRUVIUS DI DALAM ARSITEKTUR - Nurfadhillah, Ulfaizah Sahril; Saputra, Wahyu; Munandar, Munarsi (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2023)
This study aims to delve deeper into the concept of utility (function) based on Vitruvius's trilogy in architecture. The research employs a literature review, focusing on the perspectives of experts, architects, and findings from scholarly articles discussing or mentioning the concept of utility (function) in architecture. These insights are then synthesized to gain a more profound understanding of the concept of utility in architecture. The literature review draws from relevant books and scholarly articles aligned with the study's focus. The study's results indicate that the concept of utility or function in architecture extends beyond mere physical or material dimensions, as outlined by Vitruvius. Utility is the result of the interaction between the environment and human needs. In the concept of function, two critical aspects need to be understood: internal aspects encompassing physical, psychological, structural, and activity-related functions, and external aspects covering economic, aesthetic, cultural, social, expressive, and historical functions. Both aspects focus on enhancing the quality of life. Function in architecture not only influences the quality of life but also connects essential elements to create architectural works considered ideal from a human perspective. There is an intrinsic relationship between utility, venustas, and firmitas that shapes the essence of architectural utility or function itself.